ALCOHOL USE DISORDER AND ITS ADVERSE HEALTH OUTCOMES: A NARRATIVE REVIEW ON POLICY, CLINICAL INTERVENTIONS, AND FUTURE DIRECTIONS - Usman Jaffer; Farra Afieqa Rosli; Nur Rasyidah Najihah Rosli; Qistina Dayana Md Sani; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Alcohol Use Disorder (AUD), clinically recognised in the DSM-5-TR, continues to pose significant health challenges globally. This narrative review synthesises the evidence linking chronic, excessive alcohol consumption to a spectrum of adverse health outcomes, including alcohol-related liver disease (ALD), fetal alcohol spectrum disorders (FASD), various cancers, and cardiovascular diseases (CVD). Mechanistic underpinnings highlight how ethanol metabolism produces toxic metabolites that damage multiple organ systems and increase susceptibility to malignant processes, as well as how prenatal and even paternal alcohol exposure can lead to complex neurodevelopmental sequelae. Epidemiological data demonstrate that while low- to moderate-level drinking may variably affect cardiovascular risk, high-frequency consumption typical of addiction compounds the likelihood of morbidity and mortality. Preventive measures such as the World Health Organization’s SAFER initiative operate at the policy level by restricting access, increasing prices, and limiting advertisement. For individuals already exhibiting problematic use, pharmacotherapeutic options (e.g., Disulfiram, naltrexone, acamprosate) can help mitigate cravings or cause aversive reactions, while integrated care models coordinate specialists across hepatology, cardiology, and addiction services to manage complex comorbidities. Peer-led support (e.g., Alcoholics Anonymous) provides cost-effective social reinforcement for sustaining sobriety. Future research priorities include multi-omics studies in ALD, longitudinal evaluations of policy efficacy, and deeper exploration of maternal and paternal alcohol effects on offspring development. By combining robust policy interventions, evidence-based treatments, and community support, public health stakeholders can better address the pervasive burden of alcohol misuse worldwide.